2020
DOI: 10.21203/rs.3.rs-34306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Designing a nursing care plan based on Johnson's behavioral model in patients with wrist joint hematoma: A case study

Abstract: BACKGROUND Nurses can diagnose patients' problems using Johnson's pattern of behavior. This model is applicable and nurses can design and implement patient-based care in a clinical setting based on this model. This study was designed to use Johnson's behavioral model in the care of a middle-aged woman suffering from pain, edema and severe left wrist hematoma. Methods This study was conducted with the aim of determine the nursing care plan based on Johnson's behavioral model in patient with wrist joint hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Based on the ndings of the present study, there was a decrease in the patient's problems with regard to the dependency subsystem. In line with the results of our study, Karkhah et al reported improvement in the dependency subsystem as a result of a nursing care program based on Johnson's behavioral model in a patient with hematoma of the wrist joint who was admitted in Poursina Hospital in Rasht, Iran, in 2020 [20]. Suffering from heart disease is a source of stress for the patient and the family, and as a critical condition, it can disrupt the functioning and dynamics of the individual and the family.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the ndings of the present study, there was a decrease in the patient's problems with regard to the dependency subsystem. In line with the results of our study, Karkhah et al reported improvement in the dependency subsystem as a result of a nursing care program based on Johnson's behavioral model in a patient with hematoma of the wrist joint who was admitted in Poursina Hospital in Rasht, Iran, in 2020 [20]. Suffering from heart disease is a source of stress for the patient and the family, and as a critical condition, it can disrupt the functioning and dynamics of the individual and the family.…”
Section: Discussionsupporting
confidence: 90%
“…In Karkhah et al, the interventions performed to diagnose anorexia included the following: checking the patient's nutritional status, water and electrolytes, checking the patient's weight, asking the family for help in decorating the patient's food, and encouraging the patient to frequently consume food in small quantities. Based on their results, the patient's unstable behaviors regarding the ingestive subsystem were reduced following the use of Johnson's behavioral system model [20], which is in line with the results of the present study. Disease-associated malnutrition has detrimental effects on the healing process, leading to an increase in infection, delayed recovery, prolonged hospitalization, increased hospital costs, and mortality.…”
Section: Discussionsupporting
confidence: 85%
“…However, studies also show that the model is useful in planning an effective nursing care [6,7,10,11]. The international literature has revealed that the model has a positive effect on nursing outcomes in different studies based on the Behavioural System Model in their theoretical frameworks [5,9,12,13]. It is very important to provide behavioural change in chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Each subsystem consists of four structural elements. These elements are drive, set, choice, and action [8,9]. Furthermore, in the model, Johnson classifies nursing diagnoses as various "insufficiency, discrepancy, incompatibility, and dominance" based on the individual's problems with these diagnoses.…”
Section: Msdmentioning
confidence: 99%
See 1 more Smart Citation